Hemangiosarcoma in a Dog: Unusual Presentation and Increased Survival Using a Complementary/Holistic Approach Combined with Metronomic Chemotherapy - Philip Chaikin; Anja Welihozkiy (Case Reports in Veterinary Medicine)
This case report documents the clinical and pathologic findings in a 12-year-old terrier mix with intraocular and splenic hemangiosarcoma. Pathologic findings in both the spleen and globe were consistent with hemangiosarcoma with a low mitotic count. Initial treatment consisted of enucleation and then splenectomy followed by one cycle of conventional doxorubicin chemotherapy. Due to poor tolerance, a subsequent treatment regimen consisted of metronomic chemotherapy with chlorambucil combined with an alternative/complementary regimen of I’m-Yunity (polysaccharopeptide) and Yunnan Baiyao. Follow-up thoracic radiographs and abdominal ultrasounds over a period of 24 months showed no evidence of pulmonary, hepatic, or right atrial metastases, during which time the patient had an excellent quality of life. However, shortly after achieving two-year survival, the patient developed new onset seizures unresponsive to anticonvulsant therapy. Therefore, a decision was made to euthanize the dog given that the most likely etiology of the seizures was a brain tumor. Overall, this is an exceptional treatment response given the poor survival statistics of hemangiosarcoma even with conventional chemotherapy. However, additional clinical pharmacology and clinical trial data are needed to further support the use of a complementary/holistic approach in combination with metronomic chemotherapy.